Beyond Traditional Pedagogy: The Effectiveness of Chemsite-PBL on Students' Higher-Order Thinking Skills - Ghofur, Abdul; Rahmana, Delfia Ikhlasiah; Isbadrianingtyas, Nafi; Churiwiyah, Ulfah (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2025)
Higher-order thinking is a crucial skill for students to master in the digital age. However, various findings indicate that student achievement in this aspect is very low. PBL, as a learning model believed to improve these skills, in practice, still draws criticism. In many studies, it is known that PBL is effective only when students have a good mastery of basic concepts. To bridge the research gap, Chemsite was used to strengthen these basic concepts. This study used an experimental method with 28 high school students as the research sample. Class selection was carried out randomly. This study was conducted to determine the effectiveness of the integration of the PBL model with Chemsite in training higher-order thinking skills. Based on three parameters, namely: 1) the Wilcoxon test, indicating a significant difference in pre-test and post-test scores; 2) N-Gain analysis, indicating that 60.72% of students reached the high category and the rest were in the medium category; and 3) analysis of student responses, indicating a positive response between 79% and 100%. These findings prove that the Chemsite-PBL integration is effective in training HOTS and is an answer to the classic practice of PBL. Keywords: PBL, Chemsite, HOTS, Learning Integration, Basic Concept